2014
DOI: 10.7162/s1809-977720130003000013
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of cephalometric and anthropometric measures with obstructive sleep apnea severity

Abstract: Summary Introduction: Patients with obstructive sleep apnea-hypopnea syndrome (OSAHS) often have associated changes in craniofacial morphology and distribution of body fat, either alone or in combination. Aim: To correlate cephalometric and anthropometric measures with OSAHS severity by using the apnea-hypopnea index (AHI). Method: A retrospective cephalometry study of 93 patients with OSAHS was conducted from July 2010 to July 2012. The following measurements were evaluated: body mass index (BMI), neck circum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 43 publications
2
16
1
1
Order By: Relevance
“…Several recent studies showed correlations of AHI with BMI, neck, and waist circumference, which is consistent with our study [22, 23, 39, 40]. However, there are mixed reports on better correlates, with few studies showing neck circumference as better correlated with AHI [23, 24, 39, 40], and others showing waist circumference as a better correlate [22, 41], findings which are consistent with our study. In addition, there are a few studies where BMI values are better correlates of AHI than waist and neck circumferences [42, 43].…”
Section: Discussionsupporting
confidence: 92%
“…Several recent studies showed correlations of AHI with BMI, neck, and waist circumference, which is consistent with our study [22, 23, 39, 40]. However, there are mixed reports on better correlates, with few studies showing neck circumference as better correlated with AHI [23, 24, 39, 40], and others showing waist circumference as a better correlate [22, 41], findings which are consistent with our study. In addition, there are a few studies where BMI values are better correlates of AHI than waist and neck circumferences [42, 43].…”
Section: Discussionsupporting
confidence: 92%
“…Studies followed a cross-sectional, case-control and cohort design. Most of the articles were from Brazil (35) 52 57 , 60 , 61 , 63 65 , 70 , 71 , 73 86 , 88 , 91 93 , 95 97 , 99 while the others were from Chile (5) 58 , 68 , 87 , 89 , 94 , Mexico (4) 66 , 67 , 90 , 100 , Peru (3) 62 , 69 , 72 and Argentina (2) 59 , 98 . The most frequently studied patients were those with Obstructive Sleep Apnea - Hypopnea Syndrome (OSAHS) (22) 53 , 54 , 58 – 62 , 64 69 , 74 , 75 , 79 , 81 , 86 , 87 , 90 , 94 , 97 , 98 and obesity (13) 52 , 71 , 73 , 80 , 82 85 , 91 , 92 , 95 , 99 , 100 ; other diseases included HIV/AIDS, sleep disorders, bronchiectasis, depression, stroke, epilepsy, hepatic and cardiovascular pathologies.…”
Section: Resultsmentioning
confidence: 99%
“…The depositions of fat around neck, pharyngeal structure contribute to narrowing of airway and collapsibility of upper airway. [ 18 19 ] Patients in OSA group had statistically significant lower sternomental distance, thyromental distance, and higher Mallampati grade. These measurements are representative of a short neck, crowded upper airway, and larger tongue, which are indicators of difficult airway.…”
Section: Discussionmentioning
confidence: 99%